Why a new edition of Aristotle’s Eudemian Ethics? (Circe de clásicos y modernos, 2021)
The present article contains the conference delivered by Prof. C.J. Rowe at the III International Ancient Philosophy Workshop (Buenos Aires, Argentina).There he exposes the main guidelines of the forthcoming edition of Aristotle´s Eudemian Ethics which he has prepared for the Scriptorum Classicorum BibliothecaOxoniensis.
Keywords: Aristotle; Eudemian Ethics; stemma; recensio